Initiation and propagation of small fatigue crack in beta titanium alloy observed through synchrotron radiation multiscale computed tomography. (15th March 2022) - Xue, Gaoge; Nakamura, Takashi; Fujimura, Nao; Takahashi, Kosuke; Oguma, Hiroyuki; Takeuchi, Akihisa; Uesugi, Masayuki; Uesugi, Kentaro
Highlights: Multiscale SR-CT was used to analyze the small-crack initiation and propagation. Crack shapes in low-Δ K regime are dissimilar but hardly influence d a /d N –Δ K curve. The local microstructure and its interaction with cracks were captured by nano-CT. The crack initiated inside the beta grain, which lacks alpha-phase precipitation. Abstract: Synchrotron radiation computed tomography is an emerging nondestructive method for fracture analysis in materials. Herein, the in situ small-crack growth of a beta titanium alloy, Ti–22V–4Al, was monitored by a combination of microtomography (micro-CT) and nanotomography (nano-CT). The 3D characteristics of small cracks and the corresponding stress intensity factor range (Δ K ) were obtained by micro-CT; the cracks initiated at ∼10% fatigue life. In the low-Δ K regime, the scatter of the crack aspect ratio and the deviation in the crack propagation rate were significant; however, they decreased with increasing Δ K, reflecting the microstructural effect on small-crack propagation. The microstructure of the beta titanium alloy was successfully visualized by nano-CT. Consequently, the crack-surrounding-microstructure interactions evidenced that the fatigue cracks initiated from the center of the beta grain wherein the alpha-phase was less precipitated.